2013
DOI: 10.1177/0363546513484446
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Balance Accelerometer Measure and Balance Error Scoring System in Adolescent Concussions in Sports

Abstract: Background High-technology methods demonstrate that balance problems may persist up to 30 days after a concussion, whereas with low-technology methods such as the Balance Error Scoring System (BESS), performance becomes normal after only 3 days based on previously published studies in collegiate and high school athletes. Purpose To compare the National Institutes of Health’s Balance Accelerometer Measure (BAM) with the BESS regarding the ability to detect differences in postural sway between adolescents with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 20 publications
1
62
0
Order By: Relevance
“…Using inertial sensors and accelerometers to detect postural sway, King et al reported that instrumented BESS exhibited superior sensitivity (38%) and specificity (100%) in identifying adolescents with concussion compared with clinically scored BESS sensitivity and specificity scores of 23 and 92%, respectively [26]. However, Furman et al found that clinically scored BESS is superior to Balance Accelerometer Measure (BAM) in identifying adolescents with concussion [27]. Validation of instrumented measures against the original BESS is affected by the psychometric weaknesses of BESS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using inertial sensors and accelerometers to detect postural sway, King et al reported that instrumented BESS exhibited superior sensitivity (38%) and specificity (100%) in identifying adolescents with concussion compared with clinically scored BESS sensitivity and specificity scores of 23 and 92%, respectively [26]. However, Furman et al found that clinically scored BESS is superior to Balance Accelerometer Measure (BAM) in identifying adolescents with concussion [27]. Validation of instrumented measures against the original BESS is affected by the psychometric weaknesses of BESS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent technological advancements (e.g. portable force plates, inertial sensors, accelerometers and gyroscopes) have allowed for the instrumentation of clinical balance tests that may augment clinical decisions [25][26][27][28]. To overcome cost and accessibility concerns with laboratory force plates, portable clinical force plates were developed to provide detailed objective balance assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Such systems address some of the aforementioned limitations of traditional motion capture, as they allow for inexpensive, accessible quantification of human movement, in an unconstrained environment (Giggins et al, 2013). These IMU systems have been used in the objective quantification of a range of activities, from static balance tasks (King et al, 2014, Alberts et al, 2015, Furman et al, 2013, to dynamic tasks such as the squat and single leg squat , walking (Zijlstra andHof, 2003, Yang et al, 2013) and running (Lee et al, 2010). Early work investigating the use of IMUs in balance assessment has shown that a static balance assessment, instrumented with an IMU mounted on the lumbar spine, was not as effective as the traditional subjectively scored assessment in identifying balance deficits post-concussion (Furman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These IMU systems have been used in the objective quantification of a range of activities, from static balance tasks (King et al, 2014, Alberts et al, 2015, Furman et al, 2013, to dynamic tasks such as the squat and single leg squat , walking (Zijlstra andHof, 2003, Yang et al, 2013) and running (Lee et al, 2010). Early work investigating the use of IMUs in balance assessment has shown that a static balance assessment, instrumented with an IMU mounted on the lumbar spine, was not as effective as the traditional subjectively scored assessment in identifying balance deficits post-concussion (Furman et al, 2013). More recently, King et al (2014) demonstrated improved levels of sensitivity and specificity from the instrumented balance error scoring system (BESS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation